Ensemble magnetic behavior of interacting CoFe nanoparticles - Temple, Rowan C.; Mihai, Andrei P.; Arena, Dario A.; Marrows, Christopher H. (Frontiers in Physics, 2015)
Ferromagnetic nanoparticles in the 10–14 nm size range are examined for their size and interaction dependent magnetic properties. From X-ray magnetic circular dichroism the orbital-to-spin magnetic moment ratio is determined and found to decrease significantly with particle size. This is in accordance with previous complementary studies on smaller particles and highlights the difficulty of fitting to a simple core-shell model. Vibrating sample magnetometry experiments on samples with more than 1000 particles per square micron show a wide distribution of blocking temperatures from 50 to greater than 650 K. This is attributed to the dipole-dipole magnetic coupling forces between particles. The blocking temperatures show an unexpected negative correlation with increasing particle density.